2019
DOI: 10.1128/iai.00537-19
|View full text |Cite
|
Sign up to set email alerts
|

Proximity Labeling To Map Host-Pathogen Interactions at the Membrane of a Bacterium-Containing Vacuole in Chlamydia trachomatis-Infected Human Cells

Abstract: Many intracellular bacteria, including the obligate intracellular pathogen Chlamydia trachomatis, grow within a membrane-bound bacterium-containing vacuole (BCV). Secreted cytosolic effectors modulate host activity, but an understanding of the host-pathogen interactions that occur at the BCV membrane is limited by the difficulty in purifying membrane fractions from infected host cells.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(83 citation statements)
references
References 94 publications
(222 reference statements)
4
79
0
Order By: Relevance
“…Our observation that silencing GFPT expression increases bacterial diameter strongly supports the hypothesis that UDP‐GlcNAc, or an intermediate along the HBP, is hijacked into the inclusion to fuel bacterial division, possibly by feeding peptidoglycan synthesis. Interestingly, a proximity‐based labeling assay recently described an enrichment of TG2 and GFPT1 around the inclusion, suggesting that TG2 activation and GFPT modification might be most efficient in proximity of the bacteria‐containing compartment (Olson et al , ). One recent publication showed that UDP‐GlcNAc is also used during infection to post‐translationally modify the intermediate filament vimentin and this also could contribute to significant UDP‐GlcNAc consumption in C. trachomatis infection (Tarbet et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that silencing GFPT expression increases bacterial diameter strongly supports the hypothesis that UDP‐GlcNAc, or an intermediate along the HBP, is hijacked into the inclusion to fuel bacterial division, possibly by feeding peptidoglycan synthesis. Interestingly, a proximity‐based labeling assay recently described an enrichment of TG2 and GFPT1 around the inclusion, suggesting that TG2 activation and GFPT modification might be most efficient in proximity of the bacteria‐containing compartment (Olson et al , ). One recent publication showed that UDP‐GlcNAc is also used during infection to post‐translationally modify the intermediate filament vimentin and this also could contribute to significant UDP‐GlcNAc consumption in C. trachomatis infection (Tarbet et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative proximity labeling (PL) approach, relies of the translational fusion of engineered APEX to biotinylate proteins in the vicinity of the bait [85]. In the presence of H 2 O 2 , APEX catalyzes the oxidation of biotin-phenol to the highly reactive and short-lived biotin-phenoxyl radical that subsequently reacts with electron-rich amino acids (>98% tyrosine and <2% tryptophan, cysteine [86]) of proximal proteins in a range of~20 nm [86], resulting in their biotinylation.…”
Section: Proximity-dependent Labeling Approachesmentioning
confidence: 99%
“…Lately, the Ting group further enhanced the labeling efficiency of BioID via directed evolution of the biotin ligase (now named TurboID) [ 56 ]. Thus far, proximity-labeling methods have contributed the discovery of several novel protein-protein interactions at the host-pathogen interface [ 57 , 58 , 59 ]. Last but not least, chemical crosslinking in principle can stabilize protein complexes by introducing covalent interactions.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%